Clinical-epidemiological profile of hospitalization cases by COVID-19 in the ninth health region of Paraíba, Brazil (Research, Society and Development, 2022)
Objective: To describe the clinical-epidemiological profile of cases of hospitalization due to COVID-19 in the ninth health region of Paraíba. Methodology: Descriptive observational study, with a qualitative approach, carried out at the Hospital Regional de Cajazeiras. The sample consisted of 100 medical records for the years 2020 and 2021, filed at the Hospital Epidemiological Surveillance Center of the aforementioned hospital. The medical records of individuals who were hospitalized at the HRC with a confirmed diagnosis of COVID-19 were included, and those with incomplete data and/or those who were not part of the ninth health region of Paraíba were excluded. Data collection took place from September 27th to October 8th, 2021. Results: There was an equitable division of the sample of COVID-19 cases between the years 2020 and 2021. The municipalities with the highest number of cases were: Cajazeiras (39%), Sousa (13%), São José de Piranhas (10%) and São João do Rio do Peixe (9%). There was a slight predominance of males (55%), age >60 years (55%), mixed race (69%) and ignored education (47%) or elementary school (21%). The most common risk factors were: Chronic cardiovascular diseases, including Hypertension (52%), Diabetes (24%), Smoking (15%) and Obesity (14%). Among the symptoms, the most frequent were: cough (80%), dyspnea (79%), respiratory distress (75%), low oxygen saturation (64%) and fever (61%). As for the clinical profile, most patients were not vaccinated, and of those who were, 14% received 2 doses. The most used vaccine was Coronavac/Butantan. 61% of admissions were in the COVID Ward, 58% used non-invasive ventilatory support. The mortality rate was 34%, among elderly people admitted to the ICU with invasive ventilatory support. No statistically significant results were found for the association between case evolution and risk factors. Conclusion: The cases hospitalized by COVID-19 in Paraíba presented a clinical and epidemiological profile consistent with expectations.